0540 Upper Airway Stimulation for Obstructive Sleep Apnea. (27th April 2018) - Pomerantz, J; Freedom, T; Nickley, K; Bhayani, M; Gerber, M; Freedman, N; Viola-Saltzman, M
Abstract: Introduction: Hypoglossal nerve stimulation for obstructive sleep apnea [OSA] demonstrated sustained benefits in a multicenter trial. Single-center published data showed improved results over the initial trial. Our center is a multidisciplinary sleep program. We are the first in the state of Illinois to perform this surgery, and have the highest volume in the state to date. This is a retrospective review of our first ten patients. Methods: All patients were diagnosed with OSA by either polysomnography or home sleep study. Criteria for implantation was based on the FDA guidelines including continuous positive airway pressure intolerance, body mass index [BMI] less than 32 kg/m 2, age > 22 years, and an anterior-posterior collapse pattern on drug induced sedated endoscopy. Surgeries were performed under general anesthesia. Devices were tested intraoperatively and activation occurred one month postoperatively. A titration study was performed two months postoperatively to determine the proper stimulation setting Results: 9 males and 1 female underwent implantation from September 2015 to August 2017. Mean BMI (SD) was 28.36 kg/m 2 (1.4). Most patients had a reduction in their apnea hypopnea index [AHI] from a mean of 39.5 (13.25) events/hour pre-operatively to 11.7 (8.3). One patient's AHI was reduced to only 19.4 (from 21) but had a lateral AHI of 6.3. Another patient's AHI increased from 26 to 31.5 but this patient had gained 10 pounds postoperatively. An overall success rate (greater than 50% reduction in overall AHI) occurred in 8/10 patients (80%) and in 9/10 (90%) patients when including the patient with a positional improvement. Epworth Sleepiness Scale scores were also reduced from a median (interquartile range) of 9 (7) to 8.5 (8.5) in 8/10 patients (data was missing for 2 patients). No major complications occurred during surgery. One patient required a respiratory lead replacement for a lead failure at 9 months. One other patient underwent revision of the stimulating lead due to discomfort. Conclusion: Upper airway stimulation in select patients shows promise in a multidisciplinary sleep center. Longer-term data will be beneficial in predicting outcomes. Support (If Any): NorthShore University HealthSystem internal research fund.